Environmental effects of short‐rotation woody crops for bioenergy: What is and isn't known. Issue 4 (1st August 2018) - Griffiths, Natalie A.; Rau, Benjamin M.; Vaché, Kellie B.; Starr, Gregory; Bitew, Menberu M.; Aubrey, Doug P.; Martin, James A.; Benton, Elizabeth; Jackson, C. Rhett
Abstract: Logging and mill residues are currently the largest sources of woody biomass for bioenergy in the United States, but short‐rotation woody crops (SRWCs) are expected to become a larger contributor to biomass production, primarily on lands marginal for food production. However, there are very few studies on the environmental effects of SRWCs, and most have been conducted at stand rather than at watershed scales. In this manuscript, we review the potential environmental effects of SRWCs relative to current forestry or agricultural practices and best management practices (BMPs) in the southeast United States and identify priorities and constraints for monitoring and modeling these effects. Plot‐scale field studies and a watershed‐scale modeling study found improved water quality with SRWCs compared to agricultural crops. Further, a recent watershed‐scale experiment suggests that conventional forestry BMPs are sufficient to protect water quality from SRWC silvicultural activities, but the duration of these studies is short with respect to travel times of groundwater transporting nitrate to streams. While the effects of SRWC production on carbon (C) and water budgets depend on both soil properties and previous land management, woody crops will typically sequester more C when compared with agricultural crops. The overall C offset by SRWCs will depend on a variety of management practices, the number of rotations, and climate. Effects of SRWCs on biodiversity, especially aquatic organisms, are not well studied, but a meta‐analysis found that bird and mammal biodiversity is lower in SRWC stands than unmanaged forests. Long‐term (i.e., over multiple rotations) water quality, water use, C dynamics, and soil quality studies are needed, as are larger‐scale (i.e., landscape scale) biodiversity studies, to evaluate the potential effects of SRWC production. Such research should couple field measurement and modeling approaches due to the temporal (i.e., multiple rotations) and spatial (i.e., heterogeneous landscape) scaling issues involved with SRWC production. Abstract : Evaluating the environmental effects of short‐rotation woody crop (SRWC) production for bioenergy requires watershed‐scale experiments and long‐term observations coupled with watershed‐ to landscape‐scale models. These integrative approaches can evaluate environmental effects over multiple SRWC rotations.